Determinación de metales pesados mercurio y arsenico en los sedimentos del perfil costero de la provincia de El Oro - Oviedo Córdova, Jimmy Omar (2012)
This research work was made during the months of February through May of 2011 along Coastal Profile of the Province of El Oro, there are monitoring stations includes the following ports: Low High, La Puntilla, Pt Bolivar, El Coco, jeli Pto, Pto Hualtaco, Costa Rica, Jambelí Pitahaya Pto. This research raised the following objectives: Identify the levels of mercury and arsenic in sediments in the coastal profile of the Province of El Oro evaluate the results of analyzes of the sediments obtained with the maximum permissible concentrations established by the Ministry of Environment. In the coastal profile of the Province of El Oro found levels of arsenic, with high specifically in the lace, and Pto Jambelí Bolivar where maximum permissible beyond the limits, while in Low High, El Coco, Pto Jeli, pitahaya, Costa Rica and Pto Hualtaco presented low levels of arsenic. High levels of mercury were found specifically in Low High, Pto Bolivar and Pitahaya large proportion exceeding maximum permissible limits, while the lace, Jambelí, and Pto Hualtaco Jeli have low levels of mercury and El Coco and Costa Rica did not detect the presence of this metal. It is anticipated that the arsenic and mercury contamination may be due to the mishandling of fuels such as diesel, gasoline and oil, the Gulf gas extraction, illegal mining and another may be the painting of the artisanal fishing boats and ships bananas used indiscriminately.